Microbial responses to changes in flow status in temporary headwater streams: a cross-system comparison - Febria, Catherine M.; Hosen, Jacob D.; Crump, Byron C.; Palmer, Margaret A.; Williams, D. Dudley (Frontiers in Microbiology, 2015)
Microbial communities are responsible for the bulk of biogeochemical processing in temporary headwater streams, yet there is still relatively little known about how community structure and function respond to periodic drying and re-wetting. Moreover, the ability to sample temporary habitats can be a logistical challenge due to the capability to measure and predict the timing, intensity and frequency of wet-dry events. Unsurprisingly, published datasets on microbial community structure and function are limited in scope and temporal resolution and vary widely in the molecular methods applied. We compared environmental and microbial community datasets for permanent and temporary tributaries of two different North American headwater stream systems: Speed River (Ontario, Canada) and Parkers Creek (Maryland, USA). We explored whether taxonomic diversity and community composition were altered as a result of flow permanence and compared community composition amongst streams using different 16S microbial community methods (i.e., TRFLP and Illumina MiSeq). Contrary to our hypotheses, and irrespective of method, community composition did not respond strongly to drying. Microbial community composition was related to site rather than drying condition. Additional network analysis on the Parkers Creek dataset showed that community composition shifted only slightly in response to temporary stream drying and microbial co-occurrence data indicated a shift in the central microbial relationships. We compared our results with existing published studies from around the world and found a wide range in community responses to drying. We conclude by proposing three hypotheses that may address contradictory results and, when tested across systems, may expand understanding of the responses of microbial communities in temporary streams to natural and human-induced fluctuations in flow-status and permanence.